Antivirals for adult patients hospitalised with SARS-CoV-2 infection: a randomised, phase II/III, multicentre, placebo-controlled, adaptive study, with multiple arms and stages. COALITION COVID-19 BRAZIL IX - REVOLUTIOn trialResearch in context - Israel S. Maia; Aline Marcadenti; Viviane C. Veiga; Tamiris A. Miranda; Samara P.C. Gomes; Mariana B.S. Carollo; Karina L. Negrelli; Jackeline O. Gomes; Lucas Tramujas; Erlon O. Abreu-Silva; Glauco A. Westphal; Ruthy P. Fernandes; et al. (Elsevier, 2023)
Summary: Background: Repurposed drugs for treatment of new onset disease may be an effective therapeutic shortcut. We aimed to evaluate the efficacy of repurposed antivirals compared to placebo in lowering SARS-CoV2 viral load of COVID-19 patients. Methods: REVOLUTIOn is a randomised, parallel, blinded, multistage, superiority and placebo controlled randomised trial conducted in 35 centres in Brazil. We include patients aged 18 years or older admitted to hospital with laboratory-confirmed SARS-CoV-2 infection, symptoms onset 9 days or less and SpO2 94% or lower at room air were eligible. All participants were randomly allocated to receive either atazanavir, daclatasvir or sofosbuvir/daclatasvir or placebo for 10 days. The primary outcome was the decay rate (slope) of the SARS-CoV-2 viral load logarithm assessed in the modified intention to-treat population. This trial was registered with ClinicalTrials.gov, number NCT04468087. Findings: Between February 09, 2021, and August 04, 2021, 255 participants were enrolled and randomly assigned to atazanavir (n = 64), daclatasvir (n = 66), sofosbuvir/daclatasvir (n = 67) or placebo (n = 58). Compared to placebo group, the change from baseline to day 10 in log viral load was not significantly different for any of the treatment groups (0.05 [95% CI, −0.03 to 0.12], −0.02 [95% CI, −0.09 to 0.06], and −0.03 [95% CI, −0.11 to 0.04] for atazanavir, daclatasvir and sofosbuvir/daclatasvir groups respectively). There was no significant difference in the occurrence of serious adverse events between treatment groups. Interpretation: No significant reduction in viral load was observed from the use of atazanavir, daclatasvir or sofosbuvir/daclatasvir compared to placebo in hospitalised COVID-19 patients who need oxygen support with symptoms onset 9 days or less. Funding: Ministério da Ciência, Tecnologia e Inovação (MCTI) - Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPQ); Cia Latino-Americana de Medicamentos (Clamed); Cia Industrial H. Carlos Schneider (Ciser); Hospital Research Foundation Incorporation, Australia, HCor São Paulo; Blanver Farmoquímica; Instituto de Tecnologia em Fármacos (Farmanguinhos) da Fundação Oswaldo Cruz (Fiocruz); Coordenação Geral de Planejamento Estratégico (Cogeplan)/Fiocruz; and Fundação de apoio a Fiocruz (Fiotec, VPGDI-054-FIO-20-2-13).